Drag Over A Fluid Sphere Filled With Couple Stress Due to Flow of A Couple Stress Fluid with Slip Condition - Devi, Parasa Naga Lakshmi; Meduri, Phani Kumar (Trends in Sciences, 2022)
In this article, the exact solution for a couple stress fluid flow past a fluid sphere filled with a couple stress fluid is considered using interfacial slip on the boundary. The velocity is expressed with regard to the stream function. The external velocity and internal velocity are alongside the drag coefficient. It was noticed that with the increases in slip parameter, the drag coefficient is decreasing and the inflow pattern has more circulations with more area appearing near the poles and internal flow disappears gradually. The special cases of viscous fluid, no-slip condition, and solid sphere are evaluated. A good understanding of the current and literature outcomes have been obtained, including the special case of a viscous fluid past a couple stress fluid sphere. HIGHLIGHTS The flow of couple stress fluid flow past a fluid sphere filled with couple stress fluid with slip over the surface is reported In case of no-slip condition, results are captured as s→∞. and also as μ→∞, fluid sphere can reduce to the case of a solid sphere For the case of viscous fluid can be recovered as a limiting case of the analysis by taking λ_e→∞, λ_i→∞, and χ_1→∞, χ_2→∞ GRAPHICAL ABSTRACT